Evaluasi Program Belajar Literasi-Menulis di Prodi Magister PAK STT Ekumene Jakarta Melalui Model CIPP - Andreas Fernando; Carolina Etnasari Anjaya (STT Bala Keselamatan Palu, 2022)
Abstract: This study aims to evaluate the program using the CIPP (Context Input Process and Product) model for the learning to write program in the PAK Masters Study Program, Ecumenical Theology College Jakarta, which is labeled the Active Writing Masters program. The results of this evaluation are concluded: first, in terms of context, the Master of Active Writing program is very important and needed by the PAK Masters Study Program. Second, in terms of input, the program refers to the vision and mission of the PAK Masters Study Program. Third, in terms of process, the implementation of the Master of Active Writing program has been carried out well as an extra-curricular activity. Learning materials and implementation methods are as needed. Fourth, in terms of products, the results of the program are the publication of scientific papers or student research reports in several journals. Broadly speaking, the Master of Active Writing program has answered the needs and objectives set by the PAK Masters Study Program, STT Ecumenism, Jakarta.Abstrak: Penelitian ini bertujuan melakukan evaluasi program dengan model Context Input Process and Product) terhadap program belajar menulis di prodi Magister PAK Sekolah Tinggi Teologi Ekumene Jakarta yang diberi label program Magister Aktif Menulis. Hasil evaluasi ini disimpulkan: pertama, segi konteks, program Magister Aktif Menulis sangat penting dan dibutuhkan oleh prodi Magister PAK. Kedua, segi input, program tersebut mengacu kepada visi misi prodi Magister PAK. Ketiga, segi proses, penyelenggaraan program Magister Aktif Menulis telah dilakukan dengan baik sebagai kegiatan ekstra kurikuler. Materi pembelajaran dan metode pelaksanaan sesuai dengan kebutuhan. Keempat, segi produk, hasil program tersebut yaitu diterbitkannya karya tulis ilmiah atau laporan penelitian mahasiswa pada beberapa jurnal. Secara garis besar program Magister Aktif Menulis telah menjawab kebutuhan dan tujuan yang ditetapkan prodi Magister PAK STT Ekumene Jakarta.